Taxing Windfall Profits in the Energy Sector - Baunsgaard, Thomas; Vernon, Nate. (Washington, D.C. : International Monetary Fund, 2022)
The surge in fossil fuel prices in 2022 has generated substantial windfall profits in the energy sector. Policymakers in many countries are exploring policies to tax part of these profits. Excess profits can be taxed by tax instruments targeted at economic rents that avoid discouraging investment and limit any impact on further price increases. Many fossil fuel producing countries already have an adequate rent-capturing fiscal instrument in place. Others may consider introducing a permanent tax on windfall profits from fossil fuel extraction but should be more cautious about temporary and possibly poorly designed windfall profit taxes. Given the importance of encouraging decarbonatization of energy generation, it seems counter-intuitive to introduce exceptional tax measures on renewable electricity generation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Hydrocarbon Resources; Nonrenewable Resources and Conservation